ANALISIS PERILAKU BERKENDARA PENGEMUDI TRANS JOGJA DENGAN MENGGUNAKAN TACHOMETER - Noviyanti, Dian; Munawar, Ahmad (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Tachometer is an instruments that can measure rotation speed of an object that indirectly indicate the machine rotation’s safety. One of tachometer’s installation is in Trans Jogja’s busses. Writer had done an analysis with primary data collected from speed graph reading as tachometer’s recording result; and secondary data from PT. Denso Sales Indonesia as tachometer DDD-100 distributor. The result of this research shows that the average speed of Trans Jogja busses is 42,86 km/hour in the morning; 36,5 km/hour at noon; 35,2 km/hour in the afternoon and 37,39 km/hour in the evening. Meanwhile, for the violation whereas the driver exceeds maximum vehicle speed inside a city which is 50 km/hour (according to UU No.22 Tahun 2009) is 27,45% in the morning; 12,6% at noon; 13,1% in the afternoon and 17,46% in the evening. The result of this analysis is expected to become an evaluation and can give needed recommendations for policy making to increase Trans Jogja’s level of service.